Storytelling with Data as an Active Learning Tool for C++ Programming - Chavan, Pruthviraj C.; Patil, Ajinkya K.; Waghmare, Chandan A.; Patil, Sharad D.; Chate, Ganesh R. (Journal of Engineering Education Transformations, 2025)
This study examines how second-year mechanical engineering students are taught C++ programming using the active learning strategy "Storytelling with Data. Teaching a programming language to mechanical students in their second year was difficult, especially for the direct second-year students who were not familiar with C++ programming. " 50% of students struggled on the post-unit test using previous techniques. The new method required students to write topic-based descriptions that included justifications, programs, charts, and graphics. These were turned into videos using mobile devices, and app.yoodli.ai was used to assess them for linguistic elements such as weaker words, filter words, inclusiveness, voice quality, and grammar. According to analysis, 80% of the students scored between 12 and 17 out of 20 on the quiz. To determine the statistical significance, a paired t-test can be used. The p-value (0.01844) is smaller than the set significance level (0.05). As a result, you can reject the null hypothesis. This shows that there is a statistically significant difference in student performance before and after utilizing the "Storytelling with Data" approach. Feedback emphasized the method's beneficial effects on participation, group cooperation, and conceptual understanding. This study shows how "Storytelling with Data" can improve C++ programming instruction, address issues, and promote interactive learning, which improves academic performance and comprehension.